Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4103/1735-3327.197031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of canal cleaning ability of various rotary endodontic filesin apical third: A scanning electron microscopic study

Abstract: Background:The purpose of this study was to evaluate the canal cleaning ability of three novel endodontic rotary instruments and compare with ProTaper files as a control in apical third of root canals under scanning electron microscopy (SEM).Materials and Methods:Eighty freshly extracted mandibular premolars were selected according to inclusion criteria. Buccal cusp tips were ground to ensure having a flat coronal reference point with a total tooth length of 16 mm for all samples. Teeth were divided equally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
3
3
0
Order By: Relevance
“…With all four file systems, partially uninstrumented areas with remaining debris were found in all canal sections. This finding has also been described by others (5,19,22,23). In the present study, completely cleaned root canals were not found in any group.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…With all four file systems, partially uninstrumented areas with remaining debris were found in all canal sections. This finding has also been described by others (5,19,22,23). In the present study, completely cleaned root canals were not found in any group.…”
Section: Discussionsupporting
confidence: 92%
“…Here, two reciprocal files were compared with traditionally used rotary systems (that is ProTaper file) for their canal cleaning ability and reciprocal instruments better than rotational systems for debris and smear removal. In the present study our ProTaper universal and Protaper next results similar the Jadhav's research (23).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations